Positive and Relaxed Selective Pressures Have Both Strongly Influenced the Evolution of Cryonotothenioid Fishes during Their Radiation in the Freezing Southern Ocean. (23rd March 2023) - Bilyk, Kevin T; Zhuang, Xuan; Papetti, Chiara
Abstract: Evolution in the chronic cold of the Southern Ocean has had a profound influence on the physiology of cryonotothenioid fishes. However, the suite of genetic changes underlying the physiological gains and losses in these fishes is still poorly surveyed. By identifying the genomic signatures of selection, this study aims to identify the functional classes of genes that have been changed following two major physiological transitions: the onset of freezing temperatures and the loss of hemoproteins. Looking at the changes that followed the onset of freezing temperatures, positive selective pressure was found among a set of broadly acting gene regulatory factors, suggesting a route through which cryonotothenioid gene expression has been retooled for life in the cold. Further, genes related to the cell cycle and cellular adhesion were found under positive selection suggesting that both present key challenges to life in freezing waters. By contrast, genes showing signatures of the relaxation of selective pressure showed a narrower biological impact, acting on genes related to mitochondrial function. Finally, although chronic cold-water temperatures appear correlated with substantial genetic change, the loss of hemoproteins resulted in little observable change in protein-coding genes relative to their red-blooded relatives. Combined, the influence of positive and relaxed selection shows that long-term exposure to cold has led to profound changes in cryonotothenioid genomes that may make it challenging for them to adapt to a rapidly changing climate.